Treatment of Village Fund Accounting Records in Noemuke Village - Taek, Marti; Ndun, Ariyon Stefen; Liu , Cernan H, Chr, A. (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The aim of this research is to determine and analyze the treatment of accounting for village funds in Noemuke Village, as well as its conformity with applicable laws and regulations, especially Permendagri Number 20 of 2018 concerning Village Financial Management. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. The research results show that village fund accounting records in Noemuke Village have mostly been carried out in accordance with applicable regulations, but several obstacles are still found, such as limited human resources who have competence in accounting and a lack of technical training for village officials. This research suggests the need to increase the capacity of village officials in financial management and more optimal supervision so that accountability and transparency in managing village funds can be achieved. This is to find out the treatment of accounting for village funds in Noemuke Village. The results of the research show that the head of Noemuke Village is not efficient in accounting for village funds and accountability reports. This is because the Noemuke village head is not open to the community regarding financial reports and village fund accountability reports. The village head also does not provide information regarding the final report on the use of village finances to the community and does not know the final use of existing budget funds.